The Religious Role of Promoting Extremism in the United States - Benaired, Houssem Eddine (My University, 2023)
There are many factors that contribute to the promotion of extremism throughout the world. Among these factors, religion has been identified as one that can play a significant role. This research aims to uncover the role of religion as a tool for promoting extremism by examining the case of the Nation of Islam (NOI) and its extremist promotion within the United States. This dissertation will focus on the Nation of Islam under the leadership of Wallace Fard Muhammad and his successor Elijah Poole Muhammad by providing a historical background of the group and its ties to Islam while highlighting the differences between the mainstream Islamic teachings and beliefs and those of the NOI. The aim of this work is to shed light on the extremist beliefs and practices promoted by the group in the United States while using religion as a cover. Through this research, the use of religion as means to promote extremist beliefs and practices by Nation of Islam becomes more apparent as the curtain is drawn on the core extremist teachings of the group and its outcome.
A Case Study of the Nation of Islam Under the Leadership of both Wallace Fard & Elijah Muhammad (1930-1975)
Keywords: Extremism; Promotion; Religion; Nation of Islam; Islam